Qualité des apports nutritionnels du menu servi en cantines scolaires de la région de Mostaganem - LALLOUANI, Sarra (My University, 2024)
In this study, the evaluation of the nutritional quality of meals provided in school canteens is highlighted in two primary schools in Mostaganem. Direct observations and a survey were conducted in both schools to collect qualitative and quantitative data regarding the layout of the dining areas, the diversity of foods, and student satisfaction. Nutritional analyses were also carried out to measure the macronutrient content of the meals, comparing them to standard nutritional recommendations. The survey revealed several deficiencies in the organization and operation of the observed school canteens. These deficiencies include a lack of space and comfort in the dining areas, issues with the supply of meat, fish, and water, as well as limited food variety. In terms of nutritional quality, significant variations in the intake of proteins, fats, and carbohydrates were noted, indicating deficiencies that may impact the health and development of the children. The study also shows general student satisfaction with the quality of food and services offered, though improvements are needed to enhance the appeal of the meals and the variety of dishes provided.
Keywords: School canteens; Primary schools; Nutritional quality; Mostaganem